2004
DOI: 10.1084/jem.20031791
|View full text |Cite
|
Sign up to set email alerts
|

Differential Efficacy of Caspase Inhibitors on Apoptosis Markers during Sepsis in Rats and Implication for Fractional Inhibition Requirements for Therapeutics

Abstract: A rodent model of sepsis was used to establish the relationship between caspase inhibition and inhibition of apoptotic cell death in vivo. In this model, thymocyte cell death was blocked by Bcl-2 transgene, indicating that apoptosis was predominantly dependent on the mitochondrial pathway that culminates in caspase-3 activation. Caspase inhibitors, including the selective caspase-3 inhibitor M867, were able to block apoptotic manifestations both in vitro and in vivo but with strikingly different efficacy for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 34 publications
3
39
0
1
Order By: Relevance
“…The inhibitory effect of Z-VAD-fmk (Figures 4-8) or p35 ( Figure 9 and data not shown) on sub-diploidy was much more pronounced than that on PS exposure. We do not believe that this differential inhibitory effect would be owing to differential requirement of fractional inhibition (Methot et al, 2004), because caspase inhibition by Z-VAD-fmk or p35 was complete (Figures 6c, 9c and d). Rather, we prefer the hypothesis that PS is less stringently coupled to caspase activation than DNA fragmentation associated with sub-diploidy (Hirsch et al, 1997).…”
Section: Discussionmentioning
confidence: 95%
“…The inhibitory effect of Z-VAD-fmk (Figures 4-8) or p35 ( Figure 9 and data not shown) on sub-diploidy was much more pronounced than that on PS exposure. We do not believe that this differential inhibitory effect would be owing to differential requirement of fractional inhibition (Methot et al, 2004), because caspase inhibition by Z-VAD-fmk or p35 was complete (Figures 6c, 9c and d). Rather, we prefer the hypothesis that PS is less stringently coupled to caspase activation than DNA fragmentation associated with sub-diploidy (Hirsch et al, 1997).…”
Section: Discussionmentioning
confidence: 95%
“…This is evident since caspase inhibition does not completely rescue cells from apoptosis nor prevents calpain activation. Recently, Methot et al 47,48 demonstrated that high fractional caspase inhibition was needed to block DNA fragmentation versus other apoptotic markers, leading to an overestimation of putative caspase-independent apoptotic mechanisms. 47,48 In our system, we demonstrate that caspases are fully inhibited by the pan-caspase inhibitor z-VAD-fmk, using a substrate cleavage assay (Figure 4c).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Methot et al 47,48 demonstrated that high fractional caspase inhibition was needed to block DNA fragmentation versus other apoptotic markers, leading to an overestimation of putative caspase-independent apoptotic mechanisms. 47,48 In our system, we demonstrate that caspases are fully inhibited by the pan-caspase inhibitor z-VAD-fmk, using a substrate cleavage assay (Figure 4c). Moreover, we observe saturation in the kinetics of inhibition from 10 mM doses and our results are in agreement with previous studies that describe the complete blockade of cell death in caspase-dependent in vitro models of apoptosis at the same concentrations we used.…”
Section: Discussionmentioning
confidence: 99%
“…Their Compound 34 was found in a screen for molecules that formed a thiol linkage with a cysteine in the dimeric interface of caspase 1, and it acts in a way reminiscent of the BIR3 domain of XIAP, which inhibits caspase 9 by binding to the dimer interface to prevent dimerization and activation. M867, 65 produced by Merck-Frosst, is a potent reversible caspase inhibitor selective for effector caspases 3 and 7.…”
Section: Drugsmentioning
confidence: 99%